Sleep Duration Determines Excess Body Mass Index among Young Adults in Surabaya - Niwanda Yogiswara; Widati Fatmaningrum; Lilik Herawati (Faculty of Medicine Universitas Airlangga, 2022)
Introduction: Lack of sleep duration is one of the risk factors that cause excess body mass index (BMI). One of the mechanisms are by regulating an increase in appetite and reducing the energy used. This study aimed to identify the relationship between sleep duration and excess BMI in young adults.Methods: This descriptive-analytic observational study with cross-sectional design was conducted on 70 respondents aged 18-25 years old. The primary outcomes measured were sleep duration and BMI. Sleep duration was grouped as <7 hours (short sleepers), and ≥7 hours. BMI was classified as 18.5-22.9 as normal, and ≥23 as excess BMI (including overweight and obesity) according to Asia-Pacific classification. Data were analyzed using SPSS 21 software.Results: The study showed that the prevalence of excess BMI was higher in respondents with sleep deprivation (<7 hours) of 67% compared to respondents with enough sleep of 33%. The average sleep duration was 42 minutes shorter on respondents with excess BMI with an average of 6.1 hours and 6.8 hours on normal-weight respondents. According to the results of the study, there was a significant relationship between sleep duration and excess BMI (p < 0.05).Conclusion: The study revealed that sleep duration was related with excess BMI in young adults.